Music as Gestural Language : Music and Speech in the French Enlightenment - Kaitaro, Timo; Karttunen, Assi (Vishvanatha Kaviraja Institute, 2023)
It is easy to refute the notion that music conveys meanings by pointing out how arbitrary it would be to attribute context-independent conceptual meanings to musical elements. For us modern listeners who are used to listening absolute or pure music this all makes perfect sense. However, we should not forget that music was in earlier periods thought to convey meanings which were not conceptual, but more like the gestural meanings involved in speech intonation, gestures and dance. It is this earlier rhetorical tradition with its corresponding performance tradition we must also take into consideration when we judge whether there are meanings in music or not.
Keywords: eleet; musiikki; retoriikka; estetiikka